Brevi considerazioni a margine della proposta di legge n. 387 del 2018 “Disposizioni concernenti l’esposizione del Crocifisso nelle scuole e nelle pubbliche amministrazioni” (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa − 2. Quadro normativo di riferimento − 3. Sulla valenza culturale del crocifisso − 4. Laicità, imparzialità, neutralità dei luoghi pubblici - 5. La rimozione dei crocifissi: una condotta da sanzionare? - 6. Osservazioni conclusive.Draft law n. 387/18, “Provisions concerning the crucifix exhibition in schools and public administrations”: brief reflections.ABSTRACT: The draft law n. 387 of March 26, 2018, (obligation to expose the Crucifix in schools and public administrations), is part of a complex legal-constitutional context of relations between state and religious phenomenon, characterized by multiple unresolved issues and problematic profiles. The law refers to the theory of cultural and identity value of the symbol, sustained with continuity by the administrative jurisprudence in disputes concerning the regulations governing the exposure of the crucifix. The questionability of this hermeneutical perspective, largely outdated, is clear and evident if we consider the most current judgments on the subject. The most critical issues of the current proposal will be examined.
Keywords: Simboli religiosi e abbigliamento